3x-106=46-5x

Simple and best practice solution for 3x-106=46-5x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x-106=46-5x equation:


Simplifying
3x + -106 = 46 + -5x

Reorder the terms:
-106 + 3x = 46 + -5x

Solving
-106 + 3x = 46 + -5x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '5x' to each side of the equation.
-106 + 3x + 5x = 46 + -5x + 5x

Combine like terms: 3x + 5x = 8x
-106 + 8x = 46 + -5x + 5x

Combine like terms: -5x + 5x = 0
-106 + 8x = 46 + 0
-106 + 8x = 46

Add '106' to each side of the equation.
-106 + 106 + 8x = 46 + 106

Combine like terms: -106 + 106 = 0
0 + 8x = 46 + 106
8x = 46 + 106

Combine like terms: 46 + 106 = 152
8x = 152

Divide each side by '8'.
x = 19

Simplifying
x = 19

See similar equations:

| K-2=23201.06 | | 5.5x+4=4.5x+0 | | 7x-2(x-6)=3/4(8x-12)-(5-x) | | a+1xa+3=132 | | 3z-3=18 | | -8x+2=-4x-4x+2 | | 4h-2=-6h-4 | | 89=14x+1+5x-7 | | 7-(-1)-4= | | 45-5x=-50 | | 4h-2=-6h-3 | | 8x+9=7x-3 | | 9-3h=-35 | | 10-3p=2t+5 | | 3x^2+6x+5=110 | | -36v-80=75 | | 9-3h=-36 | | 55=13x-3+3x+2 | | 3(4x-3)-(x+7)=5(10-x) | | 3r-9r=-54 | | 21x+11=10a | | -9x+3=-10x-9 | | 0*(-7)= | | 5(4-2u)=u-u-48 | | (-1+-7x)-(42+6x)=36 | | 4a-2(2a+3)=5a+4 | | 0=-10a^2+475a-2400 | | -1x+x^2=0 | | 10X+3Y=-15 | | (X+2)+72+x=180 | | 4b+7-2b=25 | | 0.3x+0.51=2(-x+0.6) |

Equations solver categories